An updated checklist of caridean shrimps of the Persian Gulf and Gulf of Oman - Ashrafi, Hossein; Dehghani, Amir; Sari, Alireza; Naderloo, Reza (Zootaxa, 2020)
The material of the present checklist has been collected from the Iranian intertidal and shallow subtidal shores of the Persian Gulf and Gulf of Oman from 2015 to 2019, in addition to re-examining all the materials deposited in the Zoological Museum of the University of Tehran. This checklist providing 16 new records for the Persian Gulf and 15 for the Gulf of Oman raised the number of recorded caridean shrimps to 109 and 49 for these gulfs, respectively. However, the actual number of these shrimps are higher than these numbers due to two facts. Firstly, most of the subtidal diverse ecosystems, e.g. coral reefs and seagrass bed have not been seriously investigated taxonomically. Secondly, there are some members of species complexes and probably some new species in the study which need to be carefully treated.
Keywords: Animals; ekosystém; Ecosystem; Oman; zvířata; Indický oceán; Decapoda (Crustacea); Decapoda; Omán; Indian Ocean